Young People, Sexuality, and HIV Prevention Within Christian Faith Communities in South Africa: A Cross-Sectional Survey - Eriksson, Elisabet (Journal of religion and health, 2014)
Faith communities exert a powerful influence on the life of their members, and studies are needed about how they may be able to influence young people's attitudes regarding sexuality and HIV prevention. Data were collected through a self-administered questionnaire from young people (811), aged 15-24 years, affiliated to the Roman Catholic Church, the Lutheran Church and the Assemblies of God. The majority of participants perceived themselves at risk of HIV infection (53 %). Premarital sexual abstinence was the most frequently (88 %) reported prevention message, followed by faithfulness (23 %), HIV testing (18 %) and condom use (17 %). Furthermore, religious affiliation was associated with education on sexuality and HIV in youth groups, with better information given to members of the Lutheran and Catholic churches. Faith communities need to strengthen their capacity to educate young people in a more holistic way about sexuality and HIV prevention.